Can Strong Creditors Inhibit Entrepreneurial Activity?. (25th April 2020) - Ersahin, Nuri; Irani, Rustom M; Waldock, Katherine
Abstract: We examine entrepreneurial activity following the staggered adoption of modern-day fraudulent transfer laws in the United States. These laws strengthen unsecured creditors' rights and are particularly important for entrepreneurs whose personal assets commingle with the firm's. Using administrative data from the U.S. Census Bureau, we document declines in startup entry—particularly among riskier entrants—and closures of existing firms after these laws pass. Firm financial data shows that entrepreneurs lower leverage by reducing demand for unsecured credit. Our results suggest that strong creditor protections can limit entrepreneurs' appetite for risk, which may reduce churning along the extensive margin among the smallest firms in the economy.